'Giving back and getting on with my life': Peer mentoring, desistance and recovery of ex-offenders. (March 2020) - Nixon, Sarah
Peer work and peer mentoring are dynamic social processes that have reciprocal benefits for both mentor and mentee in tackling issues around reoffending and substance misuse. Narratives of peer mentors and desistance were collected from probation peer mentors, Criminal Justice Drugs Team mentors and health trainers, to explore identity transformation and how the criminal justice system supports ex-offenders in desistance. Criminal justice practitioners were also interviewed to explore the importance of relational support networks. Themes that emerged from the research include the transformative potential of peer work and how peer workers can become role models for other offenders. Peer workers are 'experts by experience', using personal narratives of desistance to inspire hope in others. Influential criminal justice personnel are key to this process. Peer work can be the start of building a desisting identity, acting as a 'hook for change'. Peer workers are given spaces within criminal justice organisations to work, which fosters a sense of purpose, belonging, trust and responsibility. Seeing ex-offenders from a strengths-based perspective is integral to supporting ex-offender transition. However, peer workers are inconsistently validated by criminal justice personnel, which can impede their desistance, placing them in a liminal position.